From structure topology to chemical composition. X. Titanium silicates: the crystal structure and crystal chemistry of nechelyustovite, a group III Ti-disilicate mineral - CAMARA ARTIGAS, Fernando; Sokolova E. (Mineralogical Magazine, 2009)
The crystal structure of nechelyustovite, ideally Na(4)Ba(2)Mn(1.5)square(2.5)Ti(5)Nb(Si(2)O(7))(4)O(4)(OH)(3)F(H(2)O)(6), a 5.447(1) angstrom, b 7.157(1) angstrom, c 47.259(9) angstrom, alpha 95.759(4)degrees, beta 92.136(4)degrees, gamma 89.978(4)degrees, V 1831.7(4) angstrom(3), space group P (1) over bar, Z = 2, D(calc). 3.041 g cm(-3), from Lovozero alkaline massif, Kola Peninsula, Russia, has been solved and refined to R(1) = 13.9% on the basis of 1745 unique reflections (F(o) > 15 sigma F). Electron microprobe analysis yielded the empirical formula (Na(4.21)Mn(1.11)(2+)Ca(0.46)square(1.22))(Sigma 7.00) (Ba(1.28)Sr(0.50)K(0.30)square(0.92))(Sigma 3.00)(Ti(4.14)Nb(1.43)Mn(0.33)(2+)Fe(0.06)(3+)Al(0.04))(Sigma 6.00)(Si(8.03)O(28))O(3.99)[(OH)(2.94)F(1.06)](Sigma 4.00) (H(2)O)(6.01), Z = 2, calculated on the basis of 42 (O + F) a.p.f.u, H(2)O and OH are calculated from structure refinement (H(2)O = 6 p.f.u.; F + OH = 4 p.f.u.). The crystal structure of nechelyustovite is a combination of a TS (titanium silicate) block and an I (intermediate) block. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral). The TS block exhibits linkage and stereochemistry typical for Group III (Ti = 3 a. p.f.u.) of Ti-disilicate minerals: two H sheets connect to the O sheet such that two (Si(2)O(7)) groups link to the trans edges of a Ti octahedron of the O sheet. There are two distinct TS blocks of the same topology, TS(1) and TS(2), that differ in the cations of the O sheet, [(Na(1.5)Mn(1)square(0.5))Ti] and [(Na(2)Mn(0.5)square(0.5))Ti] (4 a.p.f.u.) respectively. The TS(1) and TS(2) blocks have two different H sheets, H(1,2) and H(3,4), where (Si(2)O(7)) groups link to [5]- and [6]-coordinated (Ti, Nb) polyhedra respectively. There are three peripheral sites, A(P)(1-3), occupied mainly by Ba (less Sr and K) at 96, 86 and 26% and one peripheral site A(P)(4) occupied by Na at 50%. There are two I blocks: the I(1) block is a layer of Ba atoms; the I(2) block consists of H2O groups and A(P)(3) atoms. TS blocks ...